2007
DOI: 10.1139/h07-039
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the A1adenosine receptor increases insulin-stimulated glucose transport in isolated rat soleus muscle

Abstract: The A1 adenosine receptor (A1AR) has been suggested to participate in insulin- and contraction-stimulated glucose transport in skeletal muscle, but the qualitative and quantitative nature of the effect are controversial. We sought to determine if A1AR is expressed in rat soleus muscle and then characterize its role in glucose transport in this muscle. A1AR mRNA and protein expression were determined by RT-PCR and Western blotting, respectively. To examine the role of adenosine in 3-O-methylglucose transport, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 38 publications
0
23
1
1
Order By: Relevance
“…In view of the expression of distinct adenosine receptors subtypes (A 1 , A 2A-2B , and A 3 ) coupled to G i /G s proteins in skeletal muscle (Ren and Stiles, 1994;Lynge and Hellsten, 2000;Reading and Barclay, 2001;Thong et al, 2007), the interstitial formation of adenosine via ecto-5Ј-PDE and ecto-5Ј-nucleotidase (Hellsten and Frandsen, 1997;Chiavegatti et al, 2008) may allow the autocrine regulation of skeletal muscle function. This is of special clinical importance because ␤ 2 -AR agonists, used for treatment of asthma or chronic obstructive pulmonary disease, transiently improve isometric and isotonic contractility of respiratory skeletal muscle, including the diaphragm (Van Der Heijden et al, 1998), which is compromised in patients with chronic obstructive pulmonary disease (Ottenheijm et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In view of the expression of distinct adenosine receptors subtypes (A 1 , A 2A-2B , and A 3 ) coupled to G i /G s proteins in skeletal muscle (Ren and Stiles, 1994;Lynge and Hellsten, 2000;Reading and Barclay, 2001;Thong et al, 2007), the interstitial formation of adenosine via ecto-5Ј-PDE and ecto-5Ј-nucleotidase (Hellsten and Frandsen, 1997;Chiavegatti et al, 2008) may allow the autocrine regulation of skeletal muscle function. This is of special clinical importance because ␤ 2 -AR agonists, used for treatment of asthma or chronic obstructive pulmonary disease, transiently improve isometric and isotonic contractility of respiratory skeletal muscle, including the diaphragm (Van Der Heijden et al, 1998), which is compromised in patients with chronic obstructive pulmonary disease (Ottenheijm et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In CNS, adenosine acts as a neuromodulator, controlling the excitatory and inhibitory synapses (Fredholm et al, 2005). Evidence showed that adenosine contributes to insulin-stimulated muscle glucose transport by activating the A 1 receptor (Thong et al, 2007) and plays a role in muscle vasodilatation acting on extraluminal A 2A receptors (Marshall, 2007). Moreover, it mediates vasoconstriction of afferent arterioles through A 1 activation, increasing intracellular calcium concentration in mouse kidney (Hansen et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…74 The effects of adenosine on insulinstimulated glucose transport in skeletal muscle are controversial, with reports of both inhibitory 75,76 and stimulatory effects (Figure 3). [77][78][79] Early studies using adenosine deaminase treatment of soleus and extensor digitorum longus muscle preparations showed an inhibitory effect of endogenous adenosine on insulin-induced glucose transport and utilization. 75,76 Subsequently, it was observed that the inhibitory action of adenosine on glucose transport into skeletal muscle was mediated via A 1 adenosine receptors (Figure 3).…”
Section: Skeletal Musclementioning
confidence: 99%